Penyusunan dan Pengembangan Alat Ukur Islamic Personality Scale (IPS) - Cintami Farmawati; Nur Hidayati (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2019)
Islamic personality could be different with other personalities which cannot be explained completely by Western personality theory. For example, Western psychology might see the concept radicalism or suicide bombings as pathological, while in Islam, it is believed to be part of a behavior that reflects self-actualization. The aim of the research is to develop and develop instruments that can measure the Islamic Personality Scale (IPS) based on the theoretical framework of personality according to Islamic teachings and test the validity and reliability of this study. The research subjects were 550 students from three different universities who were selected by quota sampling. Data is obtained through testing of measuring instruments, internal validity and development of measuring instruments. Data is analyzed using Cronbach's Alpha and Confirmatory Factor Analysis. The results showed that the scale has high reliability. Islamic personality in the research subjects included ammarah, lawwamah, and mutmainah personality.